MENINGKATKAN KETERAMPILAN MENJAHIT ROK MELALUI TEKNIK BANTUAN GARIS BAGI ANAK TUNARUNGU (Penelitian Tindakan Kelas di Kelas VIII SMP-LB Panti) - Esrawati - Esrawati (Jurnal Penelitian Pendidikan Khusus, 2012)
This research aim to to 1) knowing execution process in uplift skill to sew frock pass aid technique mark with lines and 2) please prove that line aid technique can uplift skill to sew frock at dumb student class of VIII SMP-LB Panti. This Research is lifted by using method Classroom Action Research with berkolaborasi with coleage. Data collected to observation technique and of tes, laterthen analysed qualitative and is quantitative. Result of research indicate that 1) execution process in uplift skill to sew frock with line aid technique with two cycle. Activity by following cycle path namely: planning, execution, and observation of refleksi 2) Result of study sew with aid technique mark with lines: ability sew moment child of asesmen namely: TN is ( 37,5%), FT and of RN only ( 25%). After given by study at cycle of I ability sew diametrically of TN and of FT  (100%) and RN ( 87,5%). Cycle of II, result of the obtained ability of TN also (100%), FT (92,1%) and RN  (89,5%). Thereby can be concluded that line aid technique can improve ability sew frock dumb student class of VIII SMPLB Panti.